2013
DOI: 10.1007/s11367-013-0567-3
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic matter accounting in the carbon footprint analysis of the wine chain

Abstract: Concerns about global warming led to the calculation of the carbon footprint (CF) left by human activities. The agricultural sector is a significant source of greenhouse gas (GHG) emissions, though cropland soils can also act as sinks. So far, most LCA studies on agricultural products have not considered changes in soil organic matter (SOM). This paper aimed to: (1) integrate the H,nin-Dupuis SOM model into the CF study and (2) outline the impacts of different vineyard soil management scenarios on the overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 66 publications
1
38
0
Order By: Relevance
“…The Monte Carlo analysis showed that environmental profiles are likely accurate for GWP, POCP, AP and NRF impact categories [50,125]; on the contrary, ODP values have a lower confidence, probably due to the higher uncertainty related to the statistical distribution of pesticide production data. The EP category showed variable results with a greater uncertainty for organic scenarios, but lower for conventional ones.…”
Section: Discussionmentioning
confidence: 97%
“…The Monte Carlo analysis showed that environmental profiles are likely accurate for GWP, POCP, AP and NRF impact categories [50,125]; on the contrary, ODP values have a lower confidence, probably due to the higher uncertainty related to the statistical distribution of pesticide production data. The EP category showed variable results with a greater uncertainty for organic scenarios, but lower for conventional ones.…”
Section: Discussionmentioning
confidence: 97%
“…), mainly due to reduced machinery use under biodynamic management. In addition, Bosco et al (2013) have shown that grape production emissions could be offset by carbon sequestration if adequate agronomic practices are applied, suggesting that the systems we studied were far from their mitigation potential.…”
Section: Vineyardsmentioning
confidence: 95%
“…The aims of these analyses could be the comparison between the overall impacts of different food chains, as well as the comparison between single phases. Different researches have been investigated regarding the method used to verify the sustainability of the food system [6][7][8][9][10][11][12][13][14][15][16][17] and, in particular, about the school food systems [18][19][20].…”
Section: Methodsmentioning
confidence: 99%